Comparative Analysis of "Turbo", "Reduced-Turbo", "Flower" and "Semi-Turbo" Roundabout - Tomaž Tollazzi; Tedi Zgrablić; Jure Bergoč; Marko Renčelj* (Tehnički Vjesnik, 2020)
A growing number of studies, presented in scientific and professional literature, point out a poor traffic safety characteristic of "standard" two-lane roundabouts, and lower capacity than expected. These problems are resolved in different ways in different countries; however, the most successful solution has proven to be reducing the number of conflict points. Lower number of conflict points is one of the characteristics of alternative (or unconventional or no-widespread) types of roundabouts. Alternative types of roundabout differ from "standard" two-lane roundabouts in one (or more) design elements, while the purpose of their implementation is also specific. This paper illustrates two established alternative types of roundabouts (turbo and flower roundabout), and two alternative types of roundabouts in development phase (reduced-turbo and semi-turbo roundabout), offering their detailed functional description, and comparison of their capacity and traffic safety characteristics. Comparative analyses of turbo, reduced-turbo, flower and semi-turbo roundabouts was made by evaluation approach based on simulation of traffic operating at four types of alternative design layouts, including exact geometric layout of the traffic site and the precise representation of traffic flows, with turning movements, through origin-destination matrixes. The capacity comparison was conducted by a software tool VISSIM, while the traffic safety comparison was made by a software tool SSAM. In traffic safety analyses, microsimulation was used to simulate traffic operations at various levels of traffic volume. Performance measures were obtained, including measures of traffic safety, based on conflicts estimated from trajectories generated in microsimulation. According to the results, level of traffic safety (as well as capacity) of analysed alternative types of roundabouts depends on traffic flow strength, and on numbers of right-hand and left-hand turning vehicles. Consequently, for different circumstances, there are different optimal alternative types of roundabouts.